2000
DOI: 10.1016/s1053-2498(99)00141-2
|View full text |Cite
|
Sign up to set email alerts
|

A study of craniofacial growth in infant heart transplant recipients receiving cyclosporine

Abstract: The findings of this pilot study indicated that, in general, skeletal growth of the craniofacial complex as well as axial skeletal growth was not statistically significantly altered by the immunosuppressive regimen of cyclosporine over the time period evaluated. Further longitudinal data of this study's subjects may shed more light on the possible adverse effects of cyclosporine on craniofacial growth and development in spite of the fact that no untoward correlation was found over the time period studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…It is difficult for teenagers to accept the weight gain and cushingoid features secondary to steroids, or the hirsutism and gingival hyperplasia associated with CsA. In addition, for those teenagers transplanted as infants, the gingival hyperplasia secondary to CsA may induce leonine facial features (78).…”
Section: Adolescent Issuesmentioning
confidence: 99%
“…It is difficult for teenagers to accept the weight gain and cushingoid features secondary to steroids, or the hirsutism and gingival hyperplasia associated with CsA. In addition, for those teenagers transplanted as infants, the gingival hyperplasia secondary to CsA may induce leonine facial features (78).…”
Section: Adolescent Issuesmentioning
confidence: 99%
“…In addition, for those teenagers who underwent a transplant as infants, the gingival hyperplasia secondary to cyclosporine may have induced leonine facial features. [8] …”
Section: Psychologic Issuesmentioning
confidence: 99%
“…Conclusions: These results led us to conclude that some cephalometric measurements of HIV-positive children and adolescents may be similar to those of normoreactive subjects. (Am J Orthod Dentofacial Orthop 2018;153: [26][27][28][29][30][31][32][33][34][35] W ith the implementation of highly active antiretroviral therapy (HAART) in the 1990s, patients with human immunodeficiency virus (HIV1) experienced a significant increase in their quality and expectation of life. But in a short while, the adverse effects of the combination of antiretroviral drugs began to be identified through the compromised physiologic functions in several systems and organs.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the capacity of medications and chronic systemic diseases to lead to changes in craniofacial growth and development. [23][24][25][26][27][28][29][30][31] However, no such studies of HIV/AIDS patients were found; therefore, there is no way to estimate whether the disease or its treatment can influence craniofacial growth.…”
mentioning
confidence: 99%